Planteamientos sobre la ley 819 de 2003 sobre responsabilidad y transparencia fiscal: una aproximación conceptual en Boyacá (2016)
This article presents the result of an analysis on the measurement of the effectiveness of the Law of Fiscal Responsibility and Transparency (Law 819 of 2003), which has as a starting point, a review of literature on the history and evolution of the concept decentralization, regulated by some authors from the seventeenth century to the era of neo - institutionalism and both political, economic as well as political-administrative approach. Next, a brief revision of the fiscal decentralization process in Colombia will be provided using as a reference fiscal federalism understood as the degree to which local fiscal decisions are decentralized; and lastly, the effects of structural reforms implemented in Colombia concerning fiscal decentralization and implications to fiscal responsibility and transparency in territorial entities; finally the methodology to be applied is presented, through which a descriptive study analytic is done to reach a comprehensive study in order to know how this form of organization in Colombia has evolved and its impact on the department of Boyacá, focusing the study on the effectiveness of the law 819 of 2003.